Why are political discussions with fascists impossible? Reflections on the far-right politics of silence - Suuronen, Ville (Frontiers in Political Science, 2022)
This paper argues that twentieth-century fascist political theory is characterized by the systematic attempt to abolish communication from the public realm. By offering a novel reading of one the most systematic fascist thinkers, Carl Schmitt, who is compared with Sören Kierkegaard, Aristotle, Hannah Arendt, and Walter Benjamin as well as with the Italian dictator Benito Mussolini, it is argued that Schmitt’s Weimar era thought offers a many-sided challenge to the Western tradition of political thought. Against the Aristotelian notion of politics as rhetorical persuasion and speech, Schmitt mobilizes the anti-Aristotelian political theorist, Thomas Hobbes, and an array of other thinkers for his own purposes in order to redefine “the political” as a realm of silence. For Schmitt, and for fascists more generally, the realm of the political appears as an arena in which absolute and non-negotiable existential truths collide – truths, which every political community must necessarily embody in both its constitution and spirit. Reinterpreting Schmitt’s central works by relying on a broad array of rare materials, I maintain that Schmitt’s famous criterion of the “the political” discloses the crucial moment in which communicative speech becomes impossible. It is argued that understanding the internal mechanics of twentieth century fascist political thought can be highly useful for grasping the momentum that especially far-right movements are experiencing today.